Teleworking and its impact on business productivity and job satisfaction of employees: Recent trends - Ulate Araya, Randal (2020)
In recent years it has been observed a growing interest in the study of teleworking from differentfields of economics and business management. The research has been directed toward twomain lines, the first is the involvement of telework in the quality of working life of employeeswho perform their duties with this type of work and the second is the involvement of telework onproductivity of firms implement it. This research is theoretical.Were studied the determinants of success and performance models for implementing telework.For each of them the dominant theoretical approach is identified, systematizes and integratesthe main contributions, and the possibilities for future development.